Immunolocalization of cation-chloride cotransporters in the developing and mature spinal cord of opossums, Monodelphis domestica - Phan, Ha-Loan; Pflieger, Jean-François (Frontiers in Neuroanatomy, 2013)
Spinal inhibition is required to generate coordinated outputs between antagonistic muscles during locomotion. It relies on low neuronal chloride concentration set by two cation-chloride cotransporters, NKCC1 and KCC2 which, respectively, pumps Cl- in or out of neurons. It is generally accepted that NKCC1 is gradually inactivated during development, while KCC2 is upregulated and activated, resulting in low intracellular [Cl-]. Newborn opossums are very immature but perform rhythmic and alternate movements of the forelimbs to crawl on the mother’s belly and attach to a teat. Their hindlimbs are immobile. The alternation of the forelimbs suggests that mechanisms allowing spinal inhibition are present at birth. We studied the anatomical basis of inhibition in the spinal enlargements of postnatal opossums by immunolocalizing NKCC1 and KCC2. In some specimens, motoneurons and sensory afferents were labeled with TRDA prior to immunolabeling. At birth, both NKCC1 and KCC2 are detected in the presumptive grey and white matter of the ventral and the intermediolateral cord of both enlargements, but are sparse in the dorsal horn, where KCC2 is mostly seen on a small bundle of dendrites along primary afferents. KCC2 labeling is bright and has a mesh-like appearance in the grey matter and a radial appearance in the white matter, whereas NKCC1 is pale and diffuse. The subsequent expression of the cotransporters follows general ventrodorsal and mediolateral gradients, with the lumbar segments slightly lagging the cervical segments, until the mature pattern is observed around the 5th week. At all ages studied, KCC2 labeling is strong in the periphery of neurons. NKCC1 labeling decreases and becomes more uniformly distributed in the cells with age. Despite the significant anatomical and motor differences between the forelimbs and the hindlimbs of neonatal opossums, the maturation of KCC2 and NKCC1 is quite similar in both enlargements.